2010
DOI: 10.1007/s00296-010-1641-9
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates clock gene Cryptochrome1, which may aggravates mouse anti-type II collagen antibody-induced arthritis

Abstract: Very recently, the circadian rhythm was proved to play an important role in the pathogenesis of arthritis. The role of melatonin in the development and progress of rheumatoid arthritis has been implicated for decades. This study was aimed to investigate the effect of melatonin on the expression of circadian clock genes in mouse anti-type II collagen antibody-induced arthritis (CIA). Mice were divided into 3 groups: control, CIA, and CIA + melatonin treatment (MLT). Both mRNA and protein levels of circadian clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…The authors found CLOCK upregulated after mechanical stress which identifies CLOCK as a possible mechanosensitive gene [29]. Another report demonstrated that melatonin inhibited Cryptochrome 1 in a mouse model of experimental arthritis [30]. However, no functional tests were performed to understand the link between melatonin, cryptochrome 1 and proinflammatory mechanisms [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found CLOCK upregulated after mechanical stress which identifies CLOCK as a possible mechanosensitive gene [29]. Another report demonstrated that melatonin inhibited Cryptochrome 1 in a mouse model of experimental arthritis [30]. However, no functional tests were performed to understand the link between melatonin, cryptochrome 1 and proinflammatory mechanisms [30].…”
Section: Discussionmentioning
confidence: 99%
“…Another report demonstrated that melatonin inhibited Cryptochrome 1 in a mouse model of experimental arthritis [30]. However, no functional tests were performed to understand the link between melatonin, cryptochrome 1 and proinflammatory mechanisms [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Consistently, expression of CRY 1 was markedly decreased by administration of melatonin, subsequently aggravated in mouse antitype ΙΙ collagen antibody-induced arthritis [48]. Further, a phase and amplitude of the clock genes were different between osteoarthritis fibroblast-like synovial cells (OA-FLS) and RA-FLS cells [49].…”
Section: Clock Genes and Arthritis; Cry Per And Tnf-α Exacerbate mentioning
confidence: 99%
“…As melatonin is the major product of the pineal gland, this result suggests that unlike the other autoimmune diseases we discuss in this article, melatonin may have a promoting effect in the development of RA. Although one study found that melatonin possesses dose-dependent (from 1 to 100 μg/kg) prophylactic and therapeutic effects in an adjuvant-induced arthritis rat model [97], a recent study documented that melatonin treatment (10 mg/kg) increased the severity of CIA, probably via attenuation of the expression of cryptochrome 1 [98]. These contrasting observations may result from the different dosages or different models (DBA/1 mouse vs. rat) used in these studies.…”
Section: Overview Of Autoimmune Diseases and Modulatory Effects Ofmentioning
confidence: 99%